Escalating antimicrobial resistance among Enterobacteriaceae: focus on carbapenemases. (24th July 2021) - Lynch, Joseph P.; Clark, Nina M.; Zhanel, George G.
ABSTRACT: Introduction : Over the past few decades, antimicrobial resistance (AMR) has skyrocketed globally among bacteria within the Family Enterobacteriaceae (i.e. Enterobacter spp, Klebsiella spp, Escherichia coli, Proteus spp, Serratia marcescens, Citrobacter spp, and others). Enterobacteriaceae are intestinal flora and are important pathogens in nosocomial and community settings. Enterobacteriaceae spread easily between humans and may acquire AMR via plasmids or other mobile resistance elements. The emergence and spread of multidrug resistant (MDR) clones have greatly limited therapeutic options. Some infections are untreatable with existing antimicrobials. Areas covered : The authors discuss the escalation of CRE globally, the epidemiology and outcomes of CRE infections, the optimal therapy, and the potential role of several new antimicrobials to combat MDR organisms. An exhaustive search for literature related to Enterobacteriaceae was performed using PubMed, using the following key words: antimicrobial resistance; carbapenemases; Enterobacterales; Enterobacteriaceae; Klebsiella pneumoniae; Escherichia coli ; global epidemiology; metallo-β-lactamases; multidrug resistance; New Delhi Metalloproteinase-1 (NDM-1); plasmids Expert opinion : Innovation and development of new classes of antibacterial agents are critical to expand effective therapeutic options. The authors encourage the judicious use of antibiotics and aggressive infection-control measures are essential to minimize the spread of AMR.